Direct synthesis of pyrazoles from esters using tert-butoxide-assisted C–(CO) coupling1. Issue 44 (4th June 2015) - Kim, Bo Ram; Sung, Gi Hyeon; Ryu, Ki Eun; Lee, Sang-Gyeong; Yoon, Hyo Jae; Shin, Dong-Soo; Yoon, Yong-Jin
<x xml:space="preserve">Abstract</x> A strategy to synthesize pyrazoles from esters via tert-butoxide assisted C–(CO) coupling is reported.